Toxic layering through three disciplinary lenses: childhood poisoning and street pesticide use in Cape Town, South Africa. Issue 4 (20th October 2018) - Swartz, Alison; Levine, Susan; Rother, Hanna-Andrea; Langerman, Fritha
Abstract : This article focuses on the devastating hidden perils of agricultural pesticides repurposed by informal sellers in urban South African townships to kill rats and other unwanted pests. Drawing on collaborative research techniques, we investigate the causal relationship between child poisoning episodes and the household use of illegal street pesticides. Such pesticides are used to safeguard homes from pests in an attempt to protect children from the harmful consequences of rodent bites and vectorborne diseases. Here, we consider the social injustice and economic inequality of episodes of child pesticide poisoning in the Western Cape from three disciplinary perspectives: public health, medical anthropology and fine art. We ultimately seek to demonstrate the complex relationship between the political economy of sanitation, waste removal and insecure housing, and the proliferation of rodents and other pests in urban townships. As a contribution to the medical humanities, the paper leans into different disciplines to highlight the toxic layering at play in a child pesticide poisoning event. The public health perspective focuses on the circulation of illegal street pesticides, the anthropologists focus on the experiences of the children and caregivers who are victims of poisoning, and the fine artist centres the rat within a broader environmental context. While non-toxic methods to eliminate rats and household pests are critical, longer term structural changes, through environmental and human rights activism, are necessary to ameliorate the suffering caused by poisoning. The medical and health humanities is well poised to highlight creative ways to draw public attention to these challenges, as well as to bridge the divide between science and the humanities through collaborative research efforts. With this paper we set the stage for discussing and balancing perspectives when addressing pest control in poor urban communities.